Problem definicije družinskih podjetij - Duh, Mojca (Naše gospodarstvo, 2006)
According to different estimates, family enterprises account for over two-thirds of all businesses in many developed market economies. The share of enterprises which are defined as family owned depends highly on the definition used. The lack of a universally agreed-upon definition of a family enterprise is the main reason for the fact that there are no statistics complete enough to map the presence of family enterprises throughout the world and also in Slovenia. In this paper criteria and definitions for distinguishing small and medium-sized family and non-family enterprises are proposed. The results of empirical research on the share and characteristics of Slovenian family enterprises are also presented in the paper.
Keywords: management; družinska podjetja; mala podjetja; podjetništvo; Slovenia; Slovenija